Outcome of surgical treatment of peri-implantitis: results from a 2-year prospective clinical study in humans - Serino, Giovanni; Turri, Alberto (Clinical oral implants research, 2011)
Aim: The aim of the present study was to evaluate the outcome of a surgical procedure based on pocket elimination and bone re‐contouring for the treatment of peri‐implantitis. Material and methods: The 31 subjects involved in this study presented clinical signs of peri‐implantitis at one or more dental implants (i.e. ≥6 mm pockets, bleeding on probing and/or suppuration and radiographic evidence of ≥2 mm bone loss). The patients were treated with a surgical procedure based on pocket elimination and bone re‐contouring and plaque control before and following the surgery. At the time of surgery, the amount of bone loss at implants was recorded. Results: Two years following treatment, 15 (48%) subjects had no signs of peri‐implant disease; 24 patients (77%) had no implants with a probing pocket depth of ≥6 mm associated with bleeding and/or suppuration following probing. A total of 36 implants (42%) out of the 86 with initial diagnosis of peri‐implantitis presented peri‐implant disease despite treatment. The proportion of implants that became healthy following treatment was higher for those with minor initial bone loss (2–4 mm bone loss as assessed during surgery) compared with the implants with a bone loss of ≥5 mm (74% vs. 40%). Among the 18 implants with bone loss of ≥7 mm, seven were extracted. Between the 6‐month and the 2‐year examination, healthy implants following treatment tended to remain stable, while deepening of pockets was observed for those implants with residual pockets. Conclusion: The results of this study indicated that a surgical procedure based on pocket elimination and bone re‐contouring and plaque control before and following surgery was an effective therapy for treatment of peri‐implantitis for the majority of subjects and implants. However, complete disease resolution at the site level seems to depend on the initial bone loss at implants. Implants with no signs of peri‐implantitis following treatment tended to remain healthy during the 2‐year period, while a tendency for disease progression was observed for the implants that still showed signs of peri‐implant disease following treatment. To cite this article: Serino G, Turri A. Outcome of surgical treatment of peri‐implantitis: results from a 2‐year prospective clinical study in humans. Clin. Oral Impl. Res. 22, 2011; 1214–1220. doi: 10.1111/j.1600‐0501.2010.02098.x